Characterization of Sputtered CdTe Thin Films with Electron Backscatter Diffraction and Correlation with Device Performance. (16th June 2015) - Nowell, Matthew M.; Scarpulla, Michael A.; Paudel, Naba R.; Wieland, Kristopher A.; Compaan, Alvin D.; Liu, Xiangxin
Abstract: The performance of polycrystalline CdTe photovoltaic thin films is expected to depend on the grain boundary density and corresponding grain size of the film microstructure. However, the electrical performance of grain boundaries within these films is not well understood, and can be beneficial, harmful, or neutral in terms of film performance. Electron backscatter diffraction has been used to characterize the grain size, grain boundary structure, and crystallographic texture of sputtered CdTe at varying deposition pressures before and after CdCl2 treatment in order to correlate performance with microstructure. Weak fiber textures were observed in the as-deposited films, with (111) textures present at lower deposition pressures and (110) textures observed at higher deposition pressures. The CdCl2 -treated samples exhibited significant grain recrystallization with a high fraction of twin boundaries. Good correlation of solar cell efficiency was observed with twin-corrected grain size while poor correlation was found if the twin boundaries were considered as grain boundaries in the grain size determination. This implies that the twin boundaries are neutral with respect to recombination and carrier transport.